Synthesis of large single-crystal hexagonal boron nitride grains on Cu–Ni alloy - Lu, Guangyuan; Wu, Tianru; Yuan, Qinghong; Wang, Huishan; Wang, Haomin; Ding, Feng; Xie, Xiaoming; Jiang, Mianheng (Nature communications, 2015)
Hexagonal boron nitride (h-BN) has attracted significant attention because of its superior properties as well as its potential as an ideal dielectric layer for graphene-based devices. The h-BN films obtained via chemical vapour deposition in earlier reports are always polycrystalline with small grains because of high nucleation density on substrates. Here we report the successful synthesis of large single-crystal h-BN grains on rational designed Cu–Ni alloy foils. It is found that the nucleation density can be greatly reduced to 60 per mm 2 by optimizing Ni ratio in substrates. The strategy enables the growth of single-crystal h-BN grains up to 7,500 μm 2 , approximately two orders larger than that in previous reports. This work not only provides valuable information for understanding h-BN nucleation and growth mechanisms, but also gives an effective alternative to exfoliated h-BN as a high-quality dielectric layer for large-scale nanoelectronic applications. High nucleation density has thus far limited the quality and grain size of CVD-grown hexagonal boron nitride. Here, by optimizing the Ni ratio in Cu–Ni substrates, the authors successfully reduce nucleation density and report single-crystal hexagonal boron nitride grains up to 7500 μm 2 .